Implications of draxin in neurological disorders - Shinmyo, Yohei (Frontiers in Cell and Developmental Biology, 2025)
Axon guidance proteins not only play a role in the formation of proper neural circuits but also have other important functions, such as cell survival, migration, and proliferation in the brain. Therefore, mutations in the genes encoding these proteins frequently cause various types of neurological disorders, including psychiatric disorders and neurodegenerative diseases. We previously identified an axon guidance protein, draxin, that is essential for the development of several neural circuits and cell survival in the brain. Recently, the deletion of the draxin gene was identified in an inbred BTBR T+ Itpr3tf/J (BTBR/J) mouse, which is a widely used model of Autism Spectrum Disorder (ASD), suggesting that draxin deletion is a genetic factor for ASD-like characteristics in BTBR/J mice. In this review, I summarize the neuroanatomical abnormalities in draxin knockout mice by comparing them to BTBR/J mice and discuss the possible contributions of draxin to anatomical and behavioral phenotypes in BTBR/J mice.